Measurement of quality of higher education in European Union countries - Targaszewska, Marta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The paper presents the results of a comparative analysis of the quality of higher education in seventeen member states of the European Union in 2007. The author applies two methods of multivariate analysis. The first one is called Principal Components Analysis and the second is linear ordering. These two methods help assess the similarities and differences between countries and also place countries in order from the best to the worst. The author examines such variables as the organization of higher education and curricula, the governance of higher education institutions and funding. All of these variables influence the quality of higher education.
Mathematical Economics, 2012, Nr 8 (15), s. 135-145
Keywords: principal components analysis; measurement quality of higher education; linear ordering